Research and analysis for adaptive IFIR Filters for voice quality enhancement in wireless VoIP. (19th May 2019) - Luhach, Ravindra; Jha, Chandra K.; Luhach, Ashish Kr.
Abstract: Voice over Internet Protocol (VoIP) has emerged as one of the most significant technology in the field of communication and evolved as a substitute to the conventional communication method as the Public Switched Telephone Network (PSTN). In the traditional PSTN systems, due to dedicated communication line the voice quality is considerably good. In the same, network bandwidth is fully utilized but at the same the time it was not available for other users or services. The PSTN architecture is not flexible to converge data, video and voice traffic altogether. The research work carried out by the various researchers discussed in the literature review in section 2 focused on to improve the VoIP speech codecs and use of the optimization techniques to reduce the processing time for the same. The priority based load balancing algorithms such as scheduling algorithms were also used to minimize the delay content to achieve quality of service. The papers presents an analysis of the adaptive filtering algorithms were used to reduce the effect of the echo on the quality of speech signal in the VoIP system.